A comparative welfare analysis of the duty drawback and the common bonded warehouse schemes - Israel, Rex David C. (1993)
This study analyzes the private and social gains of two duty-free incentive schemes that are currently available to small-and medium-sized firms, namely, the duty drawback and the common bonded warehouse schemes. Private and social criteria within the cost-benefit framework were constructed to evaluate the effects of the two schemes on a representative export firm. At the firm level, the study finds that the common bonded warehouse scheme is superior to the duty drawback in effectively decreasing the cost of production and increasing profit. The study makes a modest attempt at evaluating the two schemes at the social level. With some qualifications, the common bonded warehouse scheme may also be socially superior than the duty drawback.
Keywords: Small business finance; Imports; Duty-free importation